Determination of Maintenance Intervals Using Multi-Criteria Approach to Increase Machine Availability at a Cement Company - M. Taufik, Ilham; Prasetyaningsih, Endang; P. A. Hidayat, Nita (Ann Publisher, 2023)
A downtime will decrease machine availability that will affect reliability and maintainability. If interval time between two consecutive machine failures is approach to zero, it shows that the machine reliability is low, and so the availability. In the other hand, if interval time between is high, the machine availability and reliability are high. However, the procuring cost of the machine components is expensive. The problem is what is the maintenance interval time in order to optimize machine availability and reliability. In this study, the downtime is minimized by determining maintenance intervals using a multicriteria, i.e. reliability, availability, and maintainability (RAM). The model used in this research is the Age Replacement Model. A case study of a cement company is taken to show the determination of the maintenance interval. The observation shows that the Kiln Division has the longest total downtime of 1,846 hours/year although the Kiln Division has implemented overhaul during 15 days and maintenance one times. The total downtime of the Kiln Division was caused by failure to the Grate Cooler machine by 56.582%. A maintenance interval is proposed, and the result shows that the proposed maintenance intervals reduce total downtime by 86.6% and improve machine availability by 1,8%.